A novel role for milrinone in neonatal acute limb ischaemia: successful conservative treatment of thrombotic arterial occlusion without thrombolysis. Issue 12 (2nd December 2019) - Boyd, Stephanie; Shah, Vibhuti; Belik, Jaques
Abstract : Acute neonatal limb ischaemia (NLI) is most frequently an iatrogenic complication, however, may also occur in utero due to thromboembolism. There is no widely accepted protocol for treatment of NLI and limited evidence to guide management. Thrombolysis and surgical management have been attempted, though both are associated with significant morbidities. Milrinone is a phosphodiesterase-3 inhibitor used for its vasodilatory effects on the systemic and pulmonary vasculature. There is also emerging evidence for benefit of milrinone in ameliorating ischaemia-reperfusion injury. The authors present a case report of a term infant with spontaneous perinatal acute limb ischaemia secondary to near-completely occlusive thrombosis of the right subclavian artery. The infant was successfully managed conservatively with milrinone without requirement for thrombolysis or surgical intervention. Milrinone represents a novel treatment option for neonates with acute limb ischaemia and consideration of a trial of milrinone prior to higher risk treatment options is warranted in this patient group.